2017
DOI: 10.5301/hipint.5000532
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of nondisplaced intracapsular femoral neck fractures with internal screw fixation in elderly patients: a systematic review

Abstract: Internal fixation with cannulated screws for UFNF in the elderly is a valuable option, although it has substantial reoperation and mortality rates. Further prospective high-quality, randomised controlled trials are required to establish the optimal approach for the treatment of UFNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 59 publications
4
58
0
3
Order By: Relevance
“…Procedure -specific complication. A slightly higher complication rate in the present study (41%) is found, when comparing the results with the literature (32.3-38.8%) [3][4][5][6][7] . Table 6 shows a detailed description of this comparison.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Procedure -specific complication. A slightly higher complication rate in the present study (41%) is found, when comparing the results with the literature (32.3-38.8%) [3][4][5][6][7] . Table 6 shows a detailed description of this comparison.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, in the meta-analysis of Pitzl and the study of Chen, there were examined displaced and undisplaced femoral neck fractures treated by head-preserving operative methods (dynamic hip screw and cannulated screws) 5,7 . In the meta-analysis of Oñativia, there were examined undisplaced femoral neck fractures treated by cannulated screw fixation 6 . In the study of Wang, there were examined displaced femoral neck fractures treated by head-preserving operative methods (dynamic hip screw or cannulated screws) 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately half of the hip fractures are femoral neck fractures. Numerous studies on the outcome of femoral neck fractures, operated by a headpreserving method, showed a high risk for osteosynthesis failure, in some cases > 40% [3][4][5][6][7][8]. In elderly patients with femoral neck fractures, artificial hip replacement should be considered [8].…”
Section: Introductionmentioning
confidence: 99%
“…Doubts have been raised regarding the results of the internal fixation of minimally displaced FNF [2]. In elderly patients, reoperation rates ranging from 8 to 19% have been reported [2][3][4][5]. The alternative treatment using hip arthroplasty is controversial.…”
Section: Introductionmentioning
confidence: 99%